Using the project-level Women’s Empowerment in Agriculture Index for Market Inclusion (pro-WEAI+MI) - Go, Ara; Paz, Florencia; Raghunathan, Kalyani; Ray, Soumyajit (International Food Policy Research Institute, 2023)
Current measures of women’s empowerment in the agricultural sector focus heavily on agricultural production. Most rural households, however, rely on multiple income streams that include processing and marketing, and many interventions focus on women’s empowerment within agricultural and non-agricultural market systems. To address these needs, we have developed the optional add-on market inclusion (+MI) modules and indicators for the pro-WEAI, along with complementary qualitative protocols. The new indicators cover aspects of intrinsic, instrumental and collective agency and of the empowerment environment that might be addressed by gender transformative value-chain focused interventions. The accompanying qualitative protocols collect data with a range of actors across the market system. This learning lab will orient participants to these +MI addon modules and the qualitative protocols and prepare them to use these resources. Overall, participants who complete this learning lab will be prepared to use proWEAI+MI in their studies. Specifically, the material covered will allow participants to: 1. Understand the evolution of the pro-WEAI+MI modules, the underlying principles of agency they are based on and their composite indicators. 2. Learn how to administer select pro-WEAI+MI modules, with the help of video demonstrations and accompanying discussions. 3. Calculate and interpret select market inclusion indicators and identify which indicators are useful for their projects—we will focus on indicator definitions and their interpretation. 4. Appreciate the value of accompanying qualitative work and incorporate the pro-WEAI+MI qualitative data collection tools into their work and interpret the findings.